2021
DOI: 10.1111/peps.12480
|View full text |Cite
|
Sign up to set email alerts
|

Retirement intention of older workers: The influences of high‐involvement work practices, individual characteristics, and economic environment

Abstract: Research on retirement decisions has invited studies to examine how personal, work-related, and environmental factors interplay to affect older workers' retirement decisions. Drawing upon the person-environment fit framework, we proposed a negative relationship between highinvolvement work practices (HIWPs) and older workers' retirement intention. We further developed hypotheses regarding the moderating effects of gender, age, educational level, managerial status, and external economic environment on the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 168 publications
1
15
0
Order By: Relevance
“…In addition to health, wealth, and family, the decision to retire is often influenced by the perceived psychosocial and psychological costs and benefits associated with work, including for example the social interactions experienced during work, feelings of personal control, accomplishment, and efficacy associated with working, self‐image, and the attachment to work relative to family roles (Barnes‐Farrell, 2003). In addition, contextual factors, such as HR policies and practices (Jiang et al., 2022, in this special issue), organizational norms regarding retirement, job characteristics, age‐related bias, and organizational climates toward age have been shown to influence older worker job transitions (see also Fisher et al., 2016, for a review of retirement timing).…”
Section: Late Career Transitions and Retirementmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to health, wealth, and family, the decision to retire is often influenced by the perceived psychosocial and psychological costs and benefits associated with work, including for example the social interactions experienced during work, feelings of personal control, accomplishment, and efficacy associated with working, self‐image, and the attachment to work relative to family roles (Barnes‐Farrell, 2003). In addition, contextual factors, such as HR policies and practices (Jiang et al., 2022, in this special issue), organizational norms regarding retirement, job characteristics, age‐related bias, and organizational climates toward age have been shown to influence older worker job transitions (see also Fisher et al., 2016, for a review of retirement timing).…”
Section: Late Career Transitions and Retirementmentioning
confidence: 99%
“…Jiang et al. (2022, this special issue) demonstrate that organizational practices influence successful aging at work. Specifically, they found that older workers’ experience of high involvement work practices (HIWPs) was negatively related to their retirement intentions, particularly among older men, older workers aged 50–59 years, older workers without a bachelor's degree, and nonmanagerial older workers.…”
Section: Additional Research Streams On the Aging Workforce In Organi...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, we know that HR systems in organizations do change over time to adapt to the changes in internal and external environments. For example, a recent study has shown that employees have become more attracted by high‐investment HR systems since the Great Recession of 2008 (Jiang, Zhang, et al, 2021). To meet employees’ increasing needs for high‐quality jobs, organizations may adjust their investment in HR systems to maintain a stable employment relationship or become prepared to deal with conflicts as the employment relationship becomes less stable.…”
Section: Opportunities Of Applying Frames Of Reference To Strategic H...mentioning
confidence: 99%
“…For the same type of HR systems, employees are also likely to have more positive reactions when they have positive attributions (Hewett et al, 2018). From the P‐E fit perspective, researchers have also found that employees tend to react to HR systems more positively when they share similar values with their organizations (Boon et al, 2011) and when their needs are satisfied by HR systems (Jiang, Zhang, et al, 2021). By examining the alignment between employees’ preferences for HR systems and HR systems used by managers, the frames of reference perspective can complement the attribution theory and the P‐E fit perspective to explain employees’ different reactions to HR systems.…”
Section: Opportunities Of Applying Frames Of Reference To Strategic H...mentioning
confidence: 99%